PENENTUAN POLA PRODUKSI MEMINIMALISASI BIAYA PADA USAHA PENGOLAHAN DODOL BANDOL DI KECAMATAN SAMBUTAN KOTA SAMARINDA (The Determination of Production Pattern to Minimize Cost at Processing Business of Dodol Bandol in Sambutan Subcity, Samarinda City) - ASMAWATI ASMAWATI; MURSIDAH MURSIDAH; SYARIFAH AIDA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2020)
Processing business of  dodol Bandol is an agroindustry which processes raw materials from agricultural products. The different of production patterns will cause the different of production cost. The purposes of this research were to know the production patterns of dodol Bandol, incremental costs of every production pattern of dodol Bandol, the minimum production cost of dodol Bandol. Methods of data analysis were descriptive and quantitative. Incremental cost was calculated for every production pattern  and then it was determined the production pattern with minimum cost. Production pattern that used is a bumpy production pattern. Incremental costs of every production patterns were constant production pattern of IDR583,120.00, bumpy production pattern of IDR117,000.00, and moderat production pattern of  IDR357,560.00. The right production pattern that could be applied on processing of dodol Bandol is bumpy production pattern because it has the lowest incremental cost among the third production patterns.